O murumuru na região do Baixo-Tocantins: características, aplicações, comercialização e rotas de processamento na empresa COFRUTA - LOPES, Wellison Marques (2019)
The present text shows important informations about the Murumuru fruit, especially for the low-Tocantins region, where many rural families live on land holdings suitable for the cultivation of the Murumuruzeiro, but often, due to misinformation, they do not see this species as a potential source of income. Thus, in the first part of the text, a bibliographical survey is presented containing citations from important authors about the Murumuru palm tree, especially with regard to its planting, its relation with the climate and the chemical composition of Murumuru fruit and butter, which is one of its main products. The second part of the text consists of a field research, with semi-structured interviews for the deputy executive director of the COFRUTA company, located in the Abaetetuba city, in the state of Pará, with the purpose of presenting how the Murumuru fruit is commercialized and used on region, as well as show the processing steps that the company performs to obtain the Murumuru butter, which, according to reports obtained in this research, works as a natural emollient that acts in the retention of skin moisture and contributes to hydration and recovery of natural elasticity